PENGARUH RUANG TERBUKA TERHADAP KINERJA PEGAWAI Kasus: Kantor Pusat BMKG Jakarta - Dedi hantono (Universitas Muhammadiyah Jakarta, 2013)
ABSTRAK. Ruang terbuka merupakan ruang yang pertama kali dirasakan setiap kali manusia memasuki suatu bangunan untuk memulai aktifitasnya termasuk ruang terbuka pada kantor. Segala sesuatu yang dirasakan pada ruang terbuka tersebut turut mempengaruhi para pegawai dalam memulai aktifitas pekerjaannya. Dalam kasus ini, Kantor Pusat BMKG yang terdiri dari beberapa massa bangunan dihubungkan oleh ruang terbuka. Oleh karenanya selain membawa dampak ketika pada saat memulai aktifitas pekerjaan, ruang terbuka ini turut dirasakan sepanjang hari karena mobilitas para pegawainya yang harus berpindah dari satu gedung ke gedung yang lain. Dampak tersebut turut pula mempengaruhi kinerja para pegawai yang bekerja di dalamnya. Kata kunci : ruang terbuka, kinerja, pegawai ABSTRACT. Open space has been determined as a space that will be faced and felt at a first time peoples entering the building to begin their activities including open space within office area. Usually all employees within office area will be affected to the ambience and atmosphere of the open space. How good or comfort the open space will affect the performance of the employees in initiating their activities. As a case study, Kantor Pusat BMKG has been conducted to represent the existence of open space within office area. This office consists some buildings which have been related by open space between buildings. Furthermore, this open space will not just affect the employees in initiating their activities but also give some impacts to the whole day’s activities. This is because the open space also has a function for employee’s mobility from one building to another. The comfort of open space will affect the performance of the employees for the whole day’s activities. Keywords : open space, performance, employee